Analysis of Clinical Characteristics and Risk Factors of Plastic Bronchitis in Children With Mycoplasma pneumoniae Pneumonia - Zhong, Haiqin; Yin, Rong; Zhao, Ran; Jiang, Kun; Sun, Chao; Dong, Xiaoyan (Frontiers in Pediatrics, 2021)
Objective: To analyze the clinical characteristics of plastic bronchitis (PB) in children with Mycoplasma pneumoniae pneumonia (MPP) in order to explore its risk factors. Methods: A retrospective analysis was performed in MPP children receiving bronchoscopy admitted to department of respiratory medicine in Shanghai Children's Hospital from January 2018 to December 2020. According to the bronchoscopic findings, the patients were divided into PB group and non-PB group. The clinical manifestations, laboratory examination, etiology, treatment methods and outcomes of the children were analyzed. Logistic regression was used to analyze the risk factors for PB in children with MPP. Results: A total of 296 children with MPP were enrolled in the study, including 42 (14.2%) children in the PB group and 254 (85.8%) children in the non-PB group. There was no difference in the ratios of gender, age, proportion of fever, cough, wet rales, and wheezing rales between the two groups(P>0.05). The univariate analysis showed that there were significant differences between the PB group and the non-PB group in LDH, D-dimer, CD3+CD4+(%), CD3+CD4+/CD3+CD8+, CD3 count, CD4 count, CD8 count, complement 3, IL8, IL-1β, IL-2, IL-10 (P<0.05). The multivariate logistic regression analysis showed that fever duration >12d, IL-8>2721.33pg/ml, LDH>482U/L and complement 3 <1.02g/L were independent risk factors for PB in children with MPP. Conclusions: Children with PB caused by MPP have protracted fever, a strong inflammatory response and immune function disturbance.